The Stylistic Essence and the Functions of Terminological Words (Texas Journal of Philology, Culture and History, 2022)
This article discusses specific features of terms in Modern English and Uzbek which studies isomorphic and allomorphic features of terms in compared languages. It investigates characteristics of different terminology, such as, linguistic, medical, physical terminology.